INTEREST TO FUTURE PROFESSIONAL ACTIVITY AS CATEGORY OF PEDAGOGICS - Andrey M. Kuzmin; Igor Yu. Sazonov; Igor V. Tarasevich (Russian State Vocational Pedagogical University, 2015)
The aim of the investigation is to study the interest to future professional activity of students of higher education institution of physical culture. Methods. The methods involve theoretical analysis of psychology and pedagogical literature; a method of the system description. Results. The various points of view concerning a phenomenon of interest and different lines of thought to definition of essence and structurization of interest to professional work are considered. Scientific novelty. The concept «interest in future professional activity» as important component of a professional orientation of the identity of the student is defined; it includes three components: cognitive, emotional and behavioural. Practical significance. The research implications can be useful while developing of pedagogical conditions on formation of students' interest in future professional activity.